When Efforts To Conceal May Actually Reveal: Whether First Amendment Protection Of Encryption Source Code and the Open Source Movement Support Re-Drawing The Constitutional Line Between the First Amendment and Copyright - Dixon, Rod (Science and Technology Law Review, 2000)
When Efforts To Conceal May Actually Reveal challenges the application of traditional copyright doctrine to computer source code. A recent decision by the Court of Appeals for the Ninth Circuit–upholding the proposition that computer source code is speech–provides a constitutional basis for reassessing the limiting principles of copyright law in the context of digital technologies. A First Amendment analysis of source code, the author contends, illuminates the failure of copyright doctrine (applying the so-called idea/expression dichotomy) to adequately calibrate the boundaries of copyright and free speech. Supporting his theoretical arguments for limiting the scope of copyright protection, the author identifies a growing movement within the computer programming community in favor of free and open access to source code. Weighing, among other things, the public policy goals underlying copyright and free speech law, the author concludes that source code should rarely be regarded as a category of expression created as a result of independent, and hence, original authorship.